The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1007/s00784-018-2418-x
|View full text |Cite
|
Sign up to set email alerts
|

Association between odontogenic conditions and maxillary sinus mucosal thickening: a retrospective CBCT study

Abstract: Maxillary sinuses are significantly influenced by various odontogenic conditions, including periodontal bone loss, periapical lesions, and missing teeth, which may result in thickening of the maxillary sinus mucosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
54
3
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(88 citation statements)
references
References 33 publications
12
54
3
8
Order By: Relevance
“…In this study, the presence of radiodensities in the maxillary sinus was found in 184 of the 408 sinuses (45.1%), considerably higher than reported in the literature [22]. On the other hand, the prevalence rate of sinus mucosal thickening was found to be 25% (n = 102 maxillary sinuses), which is much lower than in other studies (range 37-62%) [15,17,23,24]. These variations between studies may be due to differences in the measurements considered to be mucosal thickening (> 1, > 2, or > 3 mm).…”
Section: Discussioncontrasting
confidence: 66%
“…In this study, the presence of radiodensities in the maxillary sinus was found in 184 of the 408 sinuses (45.1%), considerably higher than reported in the literature [22]. On the other hand, the prevalence rate of sinus mucosal thickening was found to be 25% (n = 102 maxillary sinuses), which is much lower than in other studies (range 37-62%) [15,17,23,24]. These variations between studies may be due to differences in the measurements considered to be mucosal thickening (> 1, > 2, or > 3 mm).…”
Section: Discussioncontrasting
confidence: 66%
“…Studies evaluating the thickening of sinus mucosa in order to specify its severity level have agreed that mucosal thickening (MT) more than 2 mm is an important indicator of sinus disease (Rak et al 1991, Vallo et al 2010, Maillet et al 2011, Janner et al 2011, Lu et al 2012, Shanbhag et al 2013, Roque-Torres et al 2016, Capelli & Gatti 2016, Lathiya et al 2018, Aksoy & Orhan 2019. In addition to the thickness, the type of MT (flat or polypoid) has been considered as another important parameter for the diagnosis of OMS (Nascimento et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Aksoy and Orhan [1] evaluated tomography scans of 294 patients and determined that the thickening of the sinus mucosa was greater than 2 mm with periapical lesions coinciding with the values obtained in this study because values greater than 3 mm were obtained for both sexes; on the other hand, Aksoy and Orhan [1] obtained a significant correlation between SM and PL thickening according to age and sex, differing with this study because it was determined that if there is a correlation between LP and MS, but this is not significant for the sex variable, however, it coincides as to the moderate correlation for age for the groups of 48-59 and 60-86 years.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies that found a significant correlation between the thickening of the Schneider membrane and the periapical lesions, we have that of Aksoy and Orhan [1] because they demonstrated a direct relationship between both variables associated with age, sex, and teeth missing; Nunes et al [3] showed in their study that the posterior teeth with periapical lesions had the highest frequency of sinus anomalies, Sheikhi et al [5] in their study showed that Schneider's membrane thickening was directly related with periapical bone loss, and finally Shanbag et al [6] in their study concluded that the thickening of the Schneider membrane is significantly related to periapical lesions more frequently in the male sex.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation